Poland and the European Banking Union: to join or to wait? - Budkowska, Marta (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The aim of the article is to analyze the opportunities and risks for Poland related to the banking union. Opting in would allow Poland to strengthen integration with the European Union. Its participation in the SSM as a host country could translate into enhancing the positive image of the Polish banking market for foreign investors. Considered as a response to the global financial crisis and a mechanism to tighten the integration of the euro area, the banking union is still an incomplete project that does not include all EU Member States. Its third pillar, i.e. the Single Deposit Guarantee Scheme (SDGS), is yet to start operating. Therefore, in the case of Poland, the so-called close cooperation should be preceded by a balance of benefits and costs.